On methods of designing smartphone interface - Zhang Linghao; Liu Ying (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
The cognition, operation and experiencing of the software interface of smartphone has attracted more and more attention as the smartphone featured with surpassing the traditional-functioned featurephones turns out to be the future trend. This paper discusses the differences between smartphones and featurephones, new features of the software interface of smartphones, such as functions, size of its screen, multi-touch and intelligent sensing technology, and some peculiarities of software interface of smartphone, such as its property of being sensed or understood, efficiency and artistic quality, etc... Based on the above discussions, it proposes that the scene models and information frameworks should be constructed on the demands of users and they should be expressed by symbols. Furthermore, it discusses concrete methods of diverse design of the overall presentation of interface signs, visual style, and specific operation, etc.